Open-label study with Nalmefene as needed use in alcohol-dependent patients with evidence of elevated liver stiffness and/or hepatic steatosis - Mueller, Sebastian; Luderer, Mathias; Zhang, Doris; Meulien, Didier; Brach, Björn Steiniger; Schou, Maiken Brix (Alcohol and alcoholism, 2019)
AIMS: This open-label study in patients with alcohol dependence and evidence of elevated liver stiffness and/or hepatic steatosis was designed to explore the efficacy of nalmefene (18 mg) in reducing alcohol consumption and its subsequent effects on a variety of clinically relevant liver parameters. METHODS: Adult patients with a diagnosis of alcohol dependence and evidence of elevated liver stiffness and/or hepatic steatosis (liver stiffness >6 kPa or controlled attenuation parameter (CAP) >215 dB/m as measured by transient elastography) were recruited at two study sites in Germany. During the 12-week treatment period, patients were instructed to take nalmefene each day they perceived a risk of drinking alcohol. RESULTS: All 45 enrolled patients took at least one dose of nalmefene and 39 completed the study. After 12 weeks of study treatment with nalmefene patients showed a reduction in alcohol consumption of -13.5 days/month heavy drinking days and -45.8 g/day total alcohol consumption. Most liver parameters showed modest changes at Week 12; there was a 13% decrease in liver stiffness and 10% reduction in CAP values. Results indicated non-significant negative associations between alcohol consumption and liver stiffness and/or CAP over this 12-week study. Nalmefene was generally well tolerated, and most adverse events were mild or moderate, the most frequent being dizziness. CONCLUSIONS: Patients treated with nalmefene for 12 weeks had reductions in alcohol consumption by ~50% relative to baseline and showed trends to improvement in liver stiffness and CAP.
Gesehen am 08.02.2021